Multi-biomarker responses to estuarine habitat contamination in three fish species: Dicentrarchus labrax, Solea senegalensis and Pomatoschistus microps - Fonseca, V. F. (2020)
Several biomarker responses were determined in three fish species, Dicentrarchus labrax, Solea senegalensis and Pomatoschistus microps, from two estuaries of the Portuguese coast, Ria de Aveiro and Tejo. Both estuaries have significant anthropogenic influences from multiple sources (industrial, agricultural and shipping activities), which was evident from sediment chemical characterization concerning metal (copper, zinc, nickel, lead and chromium) and polycyclic aromatic hydrocarbon (PAH) concentrations. Spatial variability in fish responses was observed across species for most biomarkers of exposure [the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), ethoxyresorufin O-deethylase (EROD) and glutathione S-transferase (GST), and metallothionein concentrations (MT)] and effect biomarkers [lipid peroxidation (LPO), RNA to DNA ratio (R:D), protein and lipid content]. In general, the interspecific differences in biomarker responses were greater than the spatial differences, due to differences in the behavior and habitat use of the species. Nevertheless, similarities were also observed considering both chemical load and biomarker responses. In highly polluted sites fish showed in general a significant antioxidant enzyme induction, associated with decreased R:D values, while fish from the least impacted site had little enzyme induction and better condition indices (high R:D and low LPO values). EROD activity was also higher for all species in the Tejo than Ria de Aveiro estuary, despite the generally higher total PAH measured in Ria de Aveiro, most likely due to a higher proportion of 4 and 6-ring PAHs, considered more toxic than low molecular weight PAHs, in the Tejo. In conclusion, this multi-biomarker approach considering multiple species provided improved understanding of the diverse responses and effects of exposure to contaminants and the effective risk it poses for different fish species.